Validitas Buku Ensiklopedia Famili Arecaceae - Andra Puspa Abibah Wahdyah; Muhammad Zaini; Kaspul Kaspul (Mathematics Education Study Program, 2025)
21st century education requires educators to improve the quality of learning tools so that students have 4C skills. 21st century learning emphasizes learning using critical thinking skills. Development of an encyclopedia to train students' critical thinking skills. This research aims to describe the validity of the encyclopedia. This research is included in the development research (EDR) category and uses Tessmer formative evaluation research design. The expert subjects were 3 lecturers from the biology education study program at Lambung Mangkurat University. Data from the results of the encyclopedia's content validity, the instrument used is the content validation assessment sheet. The research results showed that the arecaceae family encyclopedia was declared valid